Preservice Teachers’ Perceptions of How Teachers Lead in the Classroom - Warren, Louis L. (Advances in Social Sciences Research Journal, 2023)
This study examines the perception of teacher leadership among preservice teachers and how this affects their understanding and teaching practice in an educational setting. The findings of this study indicate that preservice teachers construct their concepts of teacher leadership by observing and actively participating in the practice of teaching with their clinical teachers that include a myriad of tasks necessary for effective teaching. Initially, many preservice teachers do not realize that successful teachers are also strong leaders, and that teacher leadership exists in at different levels depending on the setting in the teaching profession. Preservice teachers’ responsibility towards teacher leadership varies. It appears that the need for reflective practice to merge their ideals of leadership with the realities is the greatest obligation they have. The level of teacher leadership education given to preservice teachers and society’s level of value for teacher leadership determine the barriers or inhibitors to preservice teachers’ development of teacher leadership competencies.